Program Corporate Social Responsibility Pertamina Aviation Hang Nadim “Desa Berdikari” in Batam - Alexius Alexius; Dadang Mashur; Dedi Kusuma Habibie (Iapa Proceedings Conference, 2020)
The purpose of this article is to frame the specific role of corporate social responsibility (CSR) by taking of regional potential development through Pertamina Aviation Hang Nadim Batam. The implementation of this corporate social responsibility (CSR) activity was carried out by Pertamina Aviation Hang Nadim of Batam. Pertamina implements corporate social responsibility (CSR) activities for people, planet, and profit purposes. During the period of June 2017-June 2018, this activities has relized 4 (four) CSR activites with the main headline “Desa Berdikari” all of which were held in Batu Besar Village, Nongsa District in Batam. The impact of this CSR activities is to reduce the number of youth dropping out of school, unemployment, as well as an increase in income, and a decrease in the number of malnutrition under-five. This article is the result of research conducted with qualitative with a describtion approach.